Strategi Calon Legislatif Perempuan Partai Kebangkitan Bangsa dalam Memenangkan Pemilihan Legislatif tahun 2024 di Kota Lhokseumawe - Yessa Marcella; Bobby Rahman; Teuku Muzaffarsyah; Muhammad Bin Abubakar; Mulyadi Mulyadi (Journal of Politics, Governance, and Administration, 2025)
This study aims to analyze the political strategies employed by female legislative candidates of the National Awakening Party (PKB) in winning the 2024 legislative election in Lhokseumawe City, Indonesia. A qualitative descriptive approach was applied, using in-depth interviews, observations, and documentation involving elected candidates, party officials, and campaign volunteers as key informants. The findings reveal that PKB female candidates adopted a strategy combining persuasive and material approaches to mobilize voter support. This strategy was implemented through social engagement activities, the utilization of women’s religious networks, and the distribution of symbolic and practical economic assistance. Beyond tactical efforts, their success was also determined by the effective use of social, cultural, and economic capital in navigating Aceh’s patriarchal socio-political structure. The study concludes that women’s political achievement in local elections is not solely shaped by affirmative policy but also by their ability to construct social legitimacy and trust among grassroots communities. This research contributes to the scholarship on gendered political strategy by highlighting how local cultural values and social relations strengthen female electability within patriarchal political systems. Abstrak Penelitian ini bertujuan untuk menganalisis strategi politik yang digunakan oleh calon legislatif perempuan Partai Kebangkitan Bangsa (PKB) dalam memenangkan Pemilihan Legislatif Tahun 2024 di Kota Lhokseumawe. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi terhadap calon legislatif terpilih, pengurus partai, serta relawan kampanye. Hasil penelitian menunjukkan bahwa calon legislatif perempuan PKB menerapkan strategi yang menggabungkan pendekatan persuasif dan materialis untuk membangun dukungan pemilih. Strategi ini diwujudkan melalui kegiatan sosial, pemanfaatan jaringan organisasi keagamaan perempuan, serta pembagian bantuan ekonomi yang bersifat simbolik dan praktis. Selain faktor strategi personal, keberhasilan mereka juga dipengaruhi oleh kemampuan memanfaatkan modal sosial, budaya, dan ekonomi dalam konteks masyarakat patriarkal Aceh. Temuan ini menegaskan bahwa keberhasilan perempuan dalam kontestasi politik lokal tidak hanya ditentukan oleh kebijakan afirmatif, tetapi juga oleh kapasitas mereka membangun legitimasi sosial di tingkat akar rumput. Penelitian ini berkontribusi pada kajian strategi politik gender dengan menunjukkan bagaimana nilai-nilai lokal dan relasi sosial digunakan untuk memperkuat elektabilitas perempuan dalam sistem politik berbasis patriarki.